ANALISIS BAHASA TUBUH GURU SEKOLAH DASAR (DI CHANNEL YOUTUBE SIGIT WAHYONO) - Sikhit Likfania Maisa; Devi Wahyu Ertanti; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Good learning management, one of which is supported by the microteaching factor of a teacher, especially the body language used. Teachers who can use body language well can create a fun learning atmosphere in the classroom. A pleasant learning atmosphere in the classroom will attract the interest and focus of students in following the learning materials presented by the teacher. Students who are interested in microteaching a teacher, students will be interested in improving their learning. If the teacher does not use body language, then learning in class will feel unpleasant so that students will feel bored and the learning material delivered by the teacher cannot be accepted optimally. Observations carried out by researchers are non-participant observations by observing videos through Sigit Wahyono's Youtube media. The approach and type of research used descriptive qualitative.Analysis of Elementary School Teacher Body Language on Sigit Wahyono's Youtube channel. The teacher uses a variety of body language variations, including eye contact, smiling, leaning forward, open posture, touch, spirit and mood, nodding and head movements, body and foot positions, hand signals, voice intonation, and facial expressions.